2019
DOI: 10.3389/fchem.2019.00615
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of CO2 Cycloaddition Reaction Catalyzed by Amine-Functionalized Ionic Liquids

Abstract: The homogeneous cycloaddition reaction of CO2 and epichlorohydrin catalyzed by amine-functionalized ionic liquid (AFIL) to yield cyclic carbonate is reported in this study. The AFIL has the dual function of ionic liquid and organic base. The experimental study indicates that AFIL can efficiently catalyze the conversion of CO2 and epichlorohydrin to the product 3-chloro-1,2-propylene. The mechanistic study based on DFT calculations reveals that the imidazolium ring in AFIL primarily catalyzes the ring-opening r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…Fairly mild conditions were used though compared to other organocatalysts. 49 Following protonation of the ionic liquid in solution, the catalyst was predicted to form cyclic carbonates by acting as a hydrogen bond donor to activate the epoxide (Scheme 1), followed by ring-opening of the epoxide by the halide anion. The ring-opened intermediate was then predicted to interact with carbon dioxide, rather than the ionic liquid catalyst.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fairly mild conditions were used though compared to other organocatalysts. 49 Following protonation of the ionic liquid in solution, the catalyst was predicted to form cyclic carbonates by acting as a hydrogen bond donor to activate the epoxide (Scheme 1), followed by ring-opening of the epoxide by the halide anion. The ring-opened intermediate was then predicted to interact with carbon dioxide, rather than the ionic liquid catalyst.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…In the same year, Liu et al studied hydroxyl-and carboxylfunctionalised imidazolium halides, 50 which were designed to activate epoxides via hydrogen bond formation followed by epoxide ring-opening by a halide, in a similar manner to Xia's DFT work. 49 The synthesis of these catalysts required palladium(II) chloride and other metal complexes, which may impact on the sustainability of this system. The most active organocatalyst 12 out of the ten bifunctional catalysts synthesised was tested against sixteen epoxides, five of which were internal epoxides, giving 87-97% isolated yields for cyclic carbonates obtained from terminal epoxides and 11-87% yields for cyclic carbonates obtained from internal epoxides.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…To provide valuable information of interaction between ILs and PO owing to the rate-determining step process of PO, [18] the optimized and lowest energy structures and interactions were presented in Figure 7. It is found that the energy between ILs of MIM-6 and PO was À 9.03 KJ mol À 1 which was the weakest.…”
Section: Interaction Between Multi-center Catalysts and Pomentioning
confidence: 99%
“…[17] Furthermore, designing ILs with specific structures of cations and anions can promote cycloaddition effectively and ideally. Chen et al [18] employed amine-functionalized ILs to produce cyclic carbonate and found that the ring-opening process was the rate-limiting step. The structures of imidazolium ILs could suit well in the cycloaddition of CO 2 and epoxides for their easier synthetic path and excellent activity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al explored whether the insertion of carbon dioxide into a P–N bond plays a positive or negative role in the reaction . Xia and co-workers studied the reaction mechanisms of CO 2 , EO, and aniline catalyzed by the binary ionic liquids BmimBr and BmimOAc and proposed a three-step parallel mechanism. Following the previous one, the reaction mechanism of SO, CO 2 , and aniline could be assumed to be mainly composed of the three steps in Scheme .…”
Section: Introductionmentioning
confidence: 99%